1996
DOI: 10.1017/s0033291700034668
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal saccadic distractibility in patients with schizophrenia: a 99mTc-HMPAO SPET study

Abstract: SynopsisRecent research has shown that some patients with schizophrenia have a severe impairment in the suppression of reflexive saccadic eye movements in the ANTI-saccade task. This saccadic distractibility has previously been found in patients with lesions of dorsolateral prefrontal cortex, implicating an abnormality of prefrontal cortex. The objective of the present study was to determine the contribution of these and other areas to the ANTI-saccadic abnormality in schizophrenia by functional neuroimaging. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 66 publications
5
30
0
1
Order By: Relevance
“…In another study,15patients with lesions restricted to the dorsolateral prefrontal cortex had difficulty in the suppression of a reflexive saccade task. Several PET or SPECT studies used the antisaccade task in healthy subjects4 13 16 17 or in patients 18. Our results are in concordance with PET studies13 16 which showed increased activity in the dorsolateral prefrontal cortex during antisaccades, and with another study17 showing no significant difference in activity in the frontal eye fields between the two tasks.…”
Section: Discussionsupporting
confidence: 90%
“…In another study,15patients with lesions restricted to the dorsolateral prefrontal cortex had difficulty in the suppression of a reflexive saccade task. Several PET or SPECT studies used the antisaccade task in healthy subjects4 13 16 17 or in patients 18. Our results are in concordance with PET studies13 16 which showed increased activity in the dorsolateral prefrontal cortex during antisaccades, and with another study17 showing no significant difference in activity in the frontal eye fields between the two tasks.…”
Section: Discussionsupporting
confidence: 90%
“…It was found that higher positive schizotypy scores 136 were associated with reduced BOLD signal in posterior and subcortical areas such as putamen, thalamus, cerebellum, and visual cortex, 137 similar to what is seen in patients with schizophrenia and their relatives. [138][139][140] Interestingly, the reductions in activation in frontal areas that are also observed in some schizophrenia studies 141,142 were not found. Neuroimaging evidence thus points to both shared networks of alteration in schizotypy and schizophrenia and differences.…”
Section: Motor Controlmentioning
confidence: 74%
“…Such deficits in suppression of reflexive saccades correlate with poor performance on WILLED ACTION AND ITS IMPAIRMENTS COGNITIVE NEU ROPSYCHOLOGY, 1998, 15 (6/7/8) cognitive tests of executive function (Paus, 1991) and are associated with decreased rCBF in the anterior cingulate, insula, and striatum (Crawford et al, 1996). Furthermore, Park and Holzman (1992) reported that patients showed similar deficits when performing a tactile or an oculomotor version of the delayed response task, thus demonstrating the generality of the problem.…”
Section: Movement Initiation and Executionmentioning
confidence: 99%